OPTIMALISASI KEAMANAN FIREWALL PADA INFRASTRUKTUR JARINGAN SMK IDN BOGOR - Yel, Mesra Betty; Mulyana, Dadang Iskandar; F, Joe Renaldy; Nurfaishal, Muhammad Dzaky; B, Muhamad Hasbi Toharudin (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
IDN Bogor Vocational High School, which was established in 2016, is known as one of the many schools that are involved in the academic, religious and IT-focused world, as its vision is